Facile fabrication of hierarchical cellulose nanospicules via hydrolytic hydrogenation. (6th March 2015) - Devarayan, Kesavan; Kim, Hak-Yong; Kim, Byoung-Suhk
Highlights: Cellulose nano-spicules, -flowers, and -rods were prepared via hydrolysis/hydrogenation. Depolymerization and deacetylation of cellulose acetate nanofibers occurs simultaneously. Novel method for production of low molecular weight saccharides. Abstract: A new spicule-like cellulose nanostructure is prepared from electrospun cellulose nanofibers using a one-pot bifunctional catalysis strategy namely hydrolytic hydrogenation. The electrospun cellulose nanofibers or cellulose film was treated in presence of catalyst consisting of an alkali and a metal to produce celluloses with structures like nanospicules, nanoflowers or nanorods, respectively. This work highlights the promising combination of electrospinning and hydrolysis/hydrogenation for facile production of hierarchical cellulose nanostructures such as nanospicules and nanorods.